Acute Effects of Spontaneous Slow Breathing and Prohibition of Media Device use on Cardiac Autonomic Function and Blood Pressure During Sleep in Young Men (Global Journal of Medical Research, 2023)
Blood pressure BP during sleep is a risk factor for cardiovascular disease Poor sleep quality leads to hypertension Sleep quality decreases with media device use and increases with deep breathing Our objective was to examine the acute effects of slow breathing and refraining from using media devices on cardiac autonomic function and blood pressure during sleep Fifteen healthy male participants were randomly assigned to one of three conditions a slow breathing BT condition 12 consecutive breaths of 4 s of inhalation through the nose 4 s pause and 8 s of exhalation approximately 3 min per breath b a BT condition BT Non-LED in which slow breathing was performed and the use of light-emitting devices LED smartphones tablets computers etc was prohibited 1 hr before bedtime and c a control condition CON in which slow breathing was not performed and the use of LED was permitted Blood pressure was measured by oscillometric method at baseline and 2 and 4 o clock at bedtime Autonomic function was measured by heart rate variability for 24 hours
Keywords: sleep; blood pressure; heart rate variability; low frequency; high frequency